Enhancement of Lipoprotein Lipase Activity by Tissue Factor Pathway Inhibitor - Mukherjee, Manjari; Kakkar, Vijay V. (Thrombosis and Haemostasis, 1999)
The effect of a basic synthetic peptide, representing the C-terminal region of tissue factor pathway inhibitor (TFPI – Lys254 - Met276), as well as that of the whole protein, on the activity of lipoprotein lipase (LPL) is described. The activity of bovine LPL was measured by chromogenic assay using a water-soluble chromogenic substrate, p-nitrophenyl butyrate. Five and 10 μM concentrations of the peptide increased Vmax of bovine LPL by 48.9% and 85.6% respectively as compared with the buffer control without affecting Km. Poly l-lysine, though positively charged did not have any effect, suggesting the importance of the amino acid sequence of the test peptide. On the other hand, 0.25, 0.5 and 1.0 mM n-butyric acid – a product of LPL catalysis in the chromogenic assay, when added to the incubation mixture decreased Vmax non competitively by 22.8%, 40.4% and 63% respectively as compared with buffer control, confirming the known product inhibition of LPL. A 100-fold molar excess of n-butyric acid produced inhibition of the LPL reaction as compared with the synthetic peptide which produced potentiation, suggesting a 1:100 stoichiometric interaction of the peptide with n-butyric acid. At a fixed concentration of 0.25 mM substrate, 10 nM full length recombinant TFPI, containing the basic C-terminal domain, increased velocity of LPL reaction by 39.4% as compared with buffer control. The same concentration of two-domain recombinant TFPI (TFPI1-160) had no effect. It is possible that negatively charged n-butyric acid is sequestered by the positively charged peptide or the basic region of recombinant full length TFPI. Relieving of product inhibition could then be a possible mechanism of the observed potentiation of bovine LPL activity by the basic peptide or full length recombinant TFPI. The 39.4% increase in reaction velocity of LPL catalysis produced by 10 nM full length recombinant TFPI was comparable to 38.9% increase produced by 5 μM of the basic peptide under the same conditions. A further increase of 78.7% was brought about by 10 μM concentration of the same peptide. The reason for about 500-fold increase in the potency of the whole protein as compared with that of the peptide is not clear. It is possible that in its tertiary conformational state, the whole protein is able to sequester product and relieve product inhibition more effectively than the short linear peptide. Rabbit polyclonal antiserum against the basic peptide partially inhibited LPL activity of human post heparin plasma, measured by radioenzymatic assay using triolein substrate. Since post heparin plasma contains full length TFPI, binding of the added antibody to its basic C-terminus and hence the relative unavailability of latter for product sequestration (oleic acid in this case) could explain the observed inhibition of human LPL activity by antibody against the peptide. Thus by enhancing lipase activity, full length TFPI may facilitate hydrolysis of triglyceride and concomitantly lower factor VII coagulant activity as demonstrated earlier, particularly after heparin injection when both TFPI and LPL are released in circulation.
Keywords: TFPI; lipoprotein lipase; p-nitrophenyl butyrate; radioenzymatic assay